Analisis Efektivitas Program Peremajaan Sawit Rakyat (PSR) pada Pekebun Sawit di Kecamatan Silangkitang Kabupaten Labuhanbatu Selatan - Syahril, Noni Malini; Sabrina, Raja; Suarti, Budi (Hasanuddin University, 2025)
The Smallholder Oil Palm Rejuvenation Program (PSR) is a national program that aims to increase the productivity of smallholder palm oil plantations by replanting old and unproductive trees to make them more sustainable and of higher quality. This research aimed to determine effectiveness of the PSR program in Silangkitang District, South Labuhanbatu Regency, through an approach that assesses the suitability of program implementation based on PSR regulations and evaluates the PSR program using the CIPP evaluation model. The research was conducted from September to November 2025. This research is quantitative descriptive with qualitative analysis. Data collection techniques used interviews and questionnaires. The research respondents were selected using random sampling, namely 51 farmers who had participated in the PSR program during the 2019-2025 period. The results of the reseacrh show that the implementation of PSR has not reached the target of 200 ha/year. The realization of rejuvenation is still hampered by farmer administration, land legality issues, the length of the technical recommendation issuance process, and farmers' concerns about losing income while the plants are not yet producing. The implementation of the PSR program still has discrepancies, especially in the plant maintenance stage, such as fertilization and pest control. The dissemination of the PSR program, ongoing guidance and monitoring for farmers by Food Security and Agriculture Agency of South Labuhanbatu District are also not yet optimal. Evaluation effectiveness of the PSR program through the CIPP evaluation model shows that it is effective. However, there are still several aspects of each CIPP component that need to be evaluated further, especially the input aspect, and follow-up is needed to improve implementation of the PSR program so that the program objectives can be achieved optimally.